2016
DOI: 10.7185/geochemlet.1705
|View full text |Cite
|
Sign up to set email alerts
|

The 176Lu-176Hf systematics of ALM-A: A sample of the recent Almahata Sitta meteorite fall.

Abstract: 176 Hf excesses, but is effectively removed by handpicking the purest mineral grains. Our study demonstrates 1) the successful application of the Lu-Hf chronometer to ALM-A, and 2) an internal consistency among the Pb-Pb age of the Solar System, the 176 Lu decay constant, the Lu-Hf CHUR parameters, and robust estimates of the 176 Hf/ 177 Hf i of the Solar System from meteorites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…(2017), Bast et al. (2017), Barnes et al. (2019), Collinet and Grove (2020a, 2020b), and Peterson et al.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…(2017), Bast et al. (2017), Barnes et al. (2019), Collinet and Grove (2020a, 2020b), and Peterson et al.…”
Section: Resultsmentioning
confidence: 98%
“…However, the bulk chemistry revealed that it is a trachyandesite (Bischoff et al, 2014). ALM-A was also studied by Amelin et al (2015), Ward et al (2017), Bast et al (2017), Barnes et al (2019), Grove (2020a, 2020b), and Peterson et al (2022). The rock mainly consists of abundant feldspar (anorthoclase and plagioclase [together ~70 vol%]) with subhedral, zoned plagioclase laths (~An 10-55 ) embedding Cr-bearing Ca pyroxene (~Fs 20-21 Wo 36-37 , Cr 2 O 3 : ~1 wt%), and Capoor pyroxene (~Fs 35-37 Wo 7-10 ; Bischoff et al, 2014;.…”
Section: Ureilitic Trachyandesitesmentioning
confidence: 87%